Application of a CC Bond‐Forming Conjugate Addition Reaction in Asymmetric Dearomatization of β‐Naphthols1. (14th July 2015) - Yang, Dongxu; Wang, Linqing; Kai, Ming; Li, Dan; Yao, Xiaojun; Wang, Rui
Abstract A CC bond‐forming conjugate reaction was successfully applied to the enantioselective dearomatization of β‐naphthols. A C(sp2)C(sp3) bond is formed by using propargylic ketones as reactive partners. Good to excellent Z/E ratios and ee values were obtained by employing an in situ generated magnesium catalyst. Further transformations of the Z‐configured CC double bond in the products were achieved under mild reaction conditions. Moreover, the stereocontrolling element of this magnesium‐catalyzed dearomatization reaction was explored by computational chemistry.